PENGARUH PROMOSI MEDIA SOSIAL INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN PRODUK STIK LABU MADU LABUQU - Tiara Ayudia Musa; Amir Halid; Echan Adam (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
IKM Al-Hidayah does not yet have accurate information about the effectiveness of promotions on social media Instagram, and how far the influence of using this media on purchasing decisions for honey pumpkin sticks. The purpose of this study is to improve the marketing of honey pumpkin stick products by utilizing social media, especially Instagram as a medium for promotion. Primary data and secondary data are the sources of research data. Hypothesis testing is used in statistical-based explanatory research to explain or validate the relationship between variables. The participants (population) of this study were LabuQu Instagram followers. Purposive sampling is the method used for sampling, and the sample amounted to 175 respondents. Using the SPSS 25 program, linear regression analysis of the data was conducted. Before the data is processed, validity, reliability, and normality tests are carried out. The results showed that promotion through Instagram social media has a positive influence on purchasing decisions for LabuQu honey pumpkin stick products by 64.2%. This influence is obtained through the t-test process, f-test, linear regression analysis, and determination test.